Indirect Impact Assessment of the road segment San Juan Nepomuceno-Ruta 6 in Paraguay - Reymondin, Louis; Arévalos, Fabiana; Palacios, Fernando; Caballero, Jazmín; Ortíz, Edder; Báez, Marcos; Arango, David; Bautista, Oscar; Yanosky, Alberto; Villalba, Alberto (Asociacion Guyra Paraguay, 2016)
This study analyzes the past, current and potential future deforestation resulting from the improvement of the road segment between San Juan Nepomuceno and the 6th route (PR-L1080) in Southeastern Paraguay. For the purpose of the analysis, the study used satellite images to detect deviations from the usual pattern of vegetation and thus identify anthropogenic change. The deforestation baseline in the study area was defined using Landsat imagery from 1987 to 2014. Using this baseline and additional datasets such as distance to roads, distance to rivers, ecosystems and elevation, a map of deforestation risk was developed at national scale and then applied in the area of influence of the studied road.